Pentingnya manajemen risiko dalam dunia bisnis modern - Nurwulandari, Alfina Dwi (Maliki Interdisciplinary Journal, 2026)
The increasingly dynamic business environment due to globalization and technological advancements has increased the level of uncertainty faced by companies. This situation demands that organizations have an effective risk management system to survive and thrive. This article aims to examine the importance of risk management in the modern business world and its role in improving organizational performance and resilience. The method used is a qualitative approach through a literature review of various current scientific sources. The study results indicate that risk management functions not only as a tool to reduce potential losses but also as a strategic instrument in decision-making and business opportunity creation. The implementation of integrated risk management enables companies to identify threats early, optimize resources, and improve operational efficiency. Furthermore, the use of technologies such as data analytics and blockchain helps strengthen transparency and accuracy in risk management. Thus, risk management is a crucial element in maintaining sustainability and increasing corporate competitiveness amidst global uncertainty.